PEMANFAATAN KOTORAN TERNAK SEBAGAI BAHAN BAKU BIOGAS PADA SIMANTRI 543 DI KECAMATAN RENDANG - Wirawan, I K. G.; Sugita, I K.G.; Suarda, M.; Atmika, I K. A. (Buletin Udayana Mengabdi; Vol 16 No 2 (2017), 2017)
Rendang is one of the eight districts in the regency of Karangasem. In this district it can be found farmer groups "Tunas Mekar Simantri 543” located in the village Pempatan. The existence of these farmer groups will prioritize the productivity of cow, where the dung is not optimally utilized as raw material biogas. The biogas management needs to be studied to determine how much methane gas generated in the reactor. This study used two methods namely: interviews with farmer groups and (ii) measuring the content of methane gas in reactor. The results that they do not understand the importance of water as mixing cow manure and methane gas production gained 41%.